DEALING WITH THE MISFITS IN AN ERP IMPLEMENTATION: EXPERIENCES FROM A UNIVERSITY CONTEXT IN INDONESIA - Fathul Wahid; Primanita Setyono (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2010)
The study aims to identify misfits in an ERP system implementation in a university context in a developingcountry with special reference to Indonesia. Various misfits related to business, information systems, and humanresources domains are identified in each stage of implementation. Diverse solutions taken to cope with themisfits are also described. We also find several lessons learned that may be adapted into a similar context ofimplementation to increase the possibilities to succeed, such as the significant role of top management support,the importance of stakeholders’ involvement, the importance of well prepared blueprint document, the criticalityof considering the context, and the significance of attention to change management process.Keywords: ERP, SAP, misfit, developing country, Indonesia, university.